Can profit sharing lower flexible outsourcing? A note - Erkki Koskela; Jan König (Institute for the Study of Labor (IZA), 2009)
We analyze the following question associated with flexible outsourcing under imperfect domestic labour market: How does the implementation of profit sharing influence flexible outsourcing? We show that in general profit sharing has a negative effect on low skilled wage and thus an outsourcing decreasing character. However due to labour union determination of effort a constant effort level will result so that in this case firm's optimal choice of profit sharing is zero.
urn:nbn:de:101:1-20090327309
Keywords: E24; J23; J33; J51; J82; 330; Flexible outsourcing; profit sharing; labour market imperfection; Outsourcing; Erfolgsbeteiligung; Theorie